2022
DOI: 10.1038/s41467-022-34415-1
|View full text |Cite
|
Sign up to set email alerts
|

CryoEM structures of the multimeric secreted NS1, a major factor for dengue hemorrhagic fever

Abstract: Dengue virus infection can cause dengue hemorrhagic fever (DHF). Dengue NS1 is multifunctional. The intracellular dimeric NS1 (iNS1) forms part of the viral replication complex. Previous studies suggest the extracellular secreted NS1 (sNS1), which is a major factor contributing to DHF, exists as hexamers. The structure of the iNS1 is well-characterised but not that of sNS1. Here we show by cryoEM that the recombinant sNS1 exists in multiple oligomeric states: the tetrameric (stable and loose conformation) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 35 publications
8
41
2
Order By: Relevance
“…In this study, we illustrated the epitopes of the five human anti-NS1 antibodies by solving the cryo-EM structures at atomic resolution. The purified sNS1 from S f 9 cells was found to mainly exist as a tetramer, consistent with the finding that the recombinant DENV2 sNS1 exists predominantly in the tetrameric form from 293F cell 28 . Our data provided detail on how five antibodies recognize the epitopes of multiple oligomeric sNS1 and the validation the function of antibodies.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we illustrated the epitopes of the five human anti-NS1 antibodies by solving the cryo-EM structures at atomic resolution. The purified sNS1 from S f 9 cells was found to mainly exist as a tetramer, consistent with the finding that the recombinant DENV2 sNS1 exists predominantly in the tetrameric form from 293F cell 28 . Our data provided detail on how five antibodies recognize the epitopes of multiple oligomeric sNS1 and the validation the function of antibodies.…”
Section: Discussionsupporting
confidence: 88%
“…Based on previous studies by Flamand et al, 1999, and Shu et al, 2022, the peak at around 300 kDa seen for WT NS1 is likely to correspond to the hexamer. Therefore, these observations imply that the I273 residue of NS1 is crucial for promoting higher-order oligomerization of the protein other than the dimers. , Tamura et al, 2022, further assessed the impact of the I273H mutation on the interaction of NS1 with membranes and observed that I273H did not alter the morphology of the liposomes, while the WT JEV NS1 was able to convert large liposomes into nanolipid structures, altering lipid membrane morphology, consistent with previous reports by Akey et al, 2014. , Therefore, it can be concluded that NS1 oligomerization into higher-order oligomers is critical for its secretion to cell culture supernatant and lipids’ membrane association . Another JEV NS1 mutant, F160D, which could not facilitate viral replication but retained the ability to secrete into the culture supernatant, demonstrated a similar capacity to modify lipid membranes as observed with the WT JEV NS1 .…”
Section: Role Of Ns1 Protein In Viral Life Cyclesupporting
confidence: 79%
“…As stated earlier, NS1 can exist in multiple oligomeric forms; it can exist as a membrane-associated dimer intracellularly (iNS1) and as a hexamer that gets secreted from the infected cells (sNS1) or remains associated with the cell surface via a GPI anchor …”
Section: Structural Arrangement Of Flavivirus Ns1 Dimer and The Hexamermentioning
confidence: 99%
See 2 more Smart Citations